On the research of multiplier effects in complex production systems - Alla N. Golovina; Victor Ye. Kovalev; Tatyana I. Malek (Journal of New Economy)
Digital transformation of institutional environment, orientation towards efficiency in the state planning, processes of new industrialisation and import sub stitution, variability of consumer behaviour, tightening competition in the new geo political realities shape the context of modern production systems’ functioning. This necessitates the modification of approaches to measuring their efficiency. The paper’s aim is to model multiplier effects in complex production systems. The concept of pro duction systems’ efficiency constitutes the methodological basis of the research. The methods include systems, comparative, and regression analysis. The evidence is eco nomic and environmental indicators of Russia’s largest metals enterprises taken from the AK&M Rating Agency and the SPARK Database for 2019–2022. The multiplier effects in complex production systems represent an extensive array of effects from technological, social, environmental, digital, and economic activities which impact on businesses’ science and technology development. The obtained regression mod els of the relationship between environmental and economic efficiencies confirm the presence of the complementary effects. This underlies the original imitation model reflecting the interaction between direct and cross effects from technological, social, environmental, digital, and economic activities of an enterprise. The findings can be practical when formulating strategies for the complex production systems develop ment.